2005
DOI: 10.1103/physrevlett.95.097002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Optical Spectral Weight in the Cuprates: Role of Electron Correlations

Abstract: We compare calculations based on the dynamical mean-field theory of the Hubbard model with the infrared spectral weight W(Omega,T) of La(2-x)SrxCuO4 and other cuprates. Without using fitting parameters we show that most of the anomalies found in W(Omega,T) with respect to normal metals, including the existence of two different energy scales for the doping and the T dependence of W(Omega,T), can be ascribed to strong correlation effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
89
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 29 publications
6
89
3
Order By: Relevance
“…For the U > U c2 calculation, we have used the scale W * = 2.25 eV to convert the theoretical results to physical units. We see that for U > U c2 the calculated spectral weight is qualitatively inconsistent with the data 16 , because it vanishes as doping tends to zero. However, we note that in the qualitative comparison, the decisive feature is the behaviour at x < 0.1 where the uncertainties in the data are largest.…”
mentioning
confidence: 39%
“…For the U > U c2 calculation, we have used the scale W * = 2.25 eV to convert the theoretical results to physical units. We see that for U > U c2 the calculated spectral weight is qualitatively inconsistent with the data 16 , because it vanishes as doping tends to zero. However, we note that in the qualitative comparison, the decisive feature is the behaviour at x < 0.1 where the uncertainties in the data are largest.…”
mentioning
confidence: 39%
“…A similar variation as large as 4 − 5% of the total SW integrated below 2.0 eV has been observed in the normal state of high-T c cuprates and quantitatively described by DMFT calculations, with the introduction of strong correlation effects [15,16]. By this approach, the temperature dependence of the SW is controlled by renormalized quasiparticle dispersion near the Fermi level.…”
mentioning
confidence: 69%
“…Recent theoretical and experimental advances have demonstrated that electronic correlations profoundly influence the optical response at energies up to several eV. [6,15,16,17,18,19]. Spectroscopic ellipsometry allows one to accurately detect such modifications and is hence a highly distinctive probe of electronic correlations in transition metal oxides [18,19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For overdoped compounds, this change is a decrease, 13,14 but for underdoped and optimal doped compounds, two groups [9][10][11][12] found an increase, though other groups found either no additional effect 15,16 or a decrease. 17 The finite cutoff was taken into account in several theoretical analyses of the T dependence of the optical integralfor instance, work based on the Hubbard model, 18 the t-J model, 14 and the d-density-wave model. 19 In Ref.…”
mentioning
confidence: 99%